Criminal Responsibility in Cybercrime: An Analysis of Phishing Crimes in Indonesia - Sari, Ratih Mega Puspa (PT. Hafasy Dwi Nawasena, 2025)
The development of digital technology has increased the complexity of cybercrimes, one of which is phishing, which is increasingly prevalent in Indonesia and causes significant losses to the community. This study aims to analyze the criminal liability of phishing perpetrators from the perspective of Indonesian criminal law and identify obstacles in law enforcement. This study uses normative juridical methods with legislative, conceptual, and case approaches, with data sources in the form of laws and regulations, academic literature, and court decisions. The results of the study show that the available legal frameworks, namely the Criminal Code, the ITE Law, and the Personal Data Protection Law, have provided a normative basis, but have not specifically regulated phishing. Law enforcement officials tend to use fraud articles (Article 378 of the Criminal Code) or electronic manipulation articles (Article 32 of the ITE Law), which cause disparities in criminal qualifications and reduce legal certainty. Proving the perpetrator's element of error (mens rea) is also still constrained by the limitations of valid digital evidence in court. These findings raise the relevance of the application of the strict liability doctrine in certain cases, as well as the importance of corporate criminal liability in situations where electronic system operators are negligent in maintaining the security of user data. In addition to normative constraints, practical obstacles are also found in the issue of cross-jurisdictional jurisdiction, given that many phishing attacks are transnational. Indonesia, which has not ratified the Budapest Convention on Cybercrime, faces limitations in international cooperation related to the extradition of perpetrators and evidence collection. The conclusion of this study emphasizes that the effectiveness of law enforcement against phishing is still limited, so it is necessary to update regulations, increase the capacity of the apparatus, implement corporate criminal responsibility, and strengthen international cooperation.